ANALYSIS OF GOVERNMENT'S ELECTRONIC MONEY POLICES IMPACT ON THE PEOPLE OF TEBING TINGGI CITY'S DECISION ON ELECTRONIC MONEY USAGE - Mariani Sinurat, Yenni; Collyn, Daniel (CV. Radja Publika, 2022)
The aim of this study is to examine the impact of government policy related to electronic money on the decisions of the people of Tebing Tinggi to use electronic money in transactions. There are at least five important government policies related to the usage of electronic money, namely policies for non-cash payment providers registered with Bank Indonesia (BI), policies for applying limits for electronic money storage balances, payment standardization policies, policies for electronic money as a substitute for tickets and policies for disbursing electronic money balances. This research was conducted to the people of Tebing Tinggi with 399 samples. Sampling using simple random sampling technique. The type of data used in this study is primary data collected using questionnaire. Methods of data analysis is using multiple linear regression analysis method. The results of the analysis show that the policies of non-cash payment providers registered with BI, policies for applying limits on electronic money storage balances, payment standardization policies, and policies for partial disbursement of electronic money balances have a positive and significant impact on the decision of the people of Tebing Tinggi to use electronic money. Meanwhile, the electronic money policy as a substitute for tickets has a positive effect but not significant.